Applying Differential Coercion and Social Support Theory to Intimate Partner Violence - Zavala, Egbert (Journal of interpersonal violence, 2021)
A review of the current body of literature on intimate partner violence (IPV) shows that the most common theories used to explain this public health issue are social learning theory, a general theory of crime, general strain theory, or a combination of these perspectives. Other criminological theories have received less empirical attention. Therefore, the purpose of this study is to apply Differential Coercion and Social Support (DCSS) theory to test its capability to explain IPV. Data collected from two public universities (N = 492) shows that three out of four measures of coercion (i.e., physical abuse, emotional abuse, and anticipated strain) predicted IPV perpetration, whereas social support was not found to be significant. Only two social-psychological deficits (anger and self-control) were found to be positive and significant in predicting IPV. Results, as well as the study’s limitations and suggestions for future research, are discussed.